The business of live music in South Africa and the jazz musician - Bruce, Emily (College of Music, 2014)
The goal of this dissertation is to investigate how the business of music operates in the live music industry of South Africa in relation to the jazz musician;; also what systems are in place that assist, protect the rights of, and provide for, the jazz musician (bearing in mind that most jazz musicians double as session musicians and dabble in various genres). Research will be conducted into what is working well within the live music industry in the UK, particularly in cities that have a rich population of active jazz performance venues and therefore, also jazz musicians. The intention for this research is to seek out the need for changes to be initiated in the South African music business with special focus on the jazz arena and particularly, conduct and legislation in the live music industry by drawing comparisons with the UK. The author's intentions are that possible alternatives will emerge during the course of this research that could increase the productivity and growth of the industry in terms of policies and systems, distribution of knowledge and access to information, successful unionisation and music business education. This study will include a component that will outline suggested key elements of the business side of music in relation to recognising the value of professional business skills for students studying jazz at tertiary level and for all professional musicians in the live music sector.